(untitled) (Nexo Revista Científica, 2021)
This paper focuses on creating a Water Refiling Station Management System (WRSMS) for selected water refilling stations in Havana, Cuba as most of them still operate by means of pen and paper, a tedious as well as time-consuming process when it comes to recording, manipulating, editing, and retrieving data, which leaves room for errors. The WRSMS is capable of storing, processing, and monitoring sales, customer, employee, inventory and attendance data, which it can be used to create financial statement reports. Furthermore, expressive investigation technique is used in this paper to assess current system of selected water stations and the WRSMS in terms of functionality and usability. It also helped to determine the noteworthy alteration among current system and WRSMS assessment. The researcher used purposive sampling technique and an industry-validated instrument to assess functionality and usability of employees from selected water stations in the area and was able to get the participation of 15 different water-refilling stations and 30 employees. Some statistical tools are used for this research paper to have sufficient evidence to conclude that the majority of employees “agree” that their current system is functional and usable. However, once presented with the WRSMS, most employees “strongly agree” that the system is more useful to handle business data. The used t-test strengthens the point that the noteworthy alteration exists among ratings of the present system in addition to WRSMS when it comes to functionality and usability.